Pengaruh Peer Education Methode Terhadap Pengetahuan Dan Sikap Remaja Di Pondok Pesantren Darusalam Algontory Batam - Kusrini, Henny; M. Noer, Rachmawaty; Agusthia, Mira (Initium Medica Journal, 2021)
This study aims to determine whether there is an effect of Peer Education Method in Preventing Covid 19 on Adolescent Knowledge and Attitudes at Pondok Pesantren Darussalam Algontory Batam City. Design This study uses a quasi-experimental one group pre-test-post test. The dependent variable is the Peer education method and the dependent variable is the knowledge and attitudes of adolescents. The total population is 56 people and the sample used is 49 teenagers. Data analysis used univariate and bivariate. The results of this study were obtained before being given the implementation of Peer Education, there were good knowledge of 6 students (12.2%). Meanwhile, after being given the implementation of Peer Education, there were 43 teenagers (87.8%) good knowledge. The attitude of teenagers before being given the Peer Education Method there were 35 teenagers who had a negative attitude and after being given the Peer Education Method there were all teenagers who had a positive attitude. Conclusion: There is an effect of the Peer Education Method on increasing the knowledge and attitudes of adolescents in preventing covid-19 at Pondok Pesantren Darusalam Algontory, Batam City. Suggestion: it is necessary to increase the knowledge and attitude of teenagers in preventing covid-19.